Research ethical committees in Scotland. Issue 6265 (28th February 1981) - Thompson, I E; French, K; Melia, K M; Boyd, K M; Templeton, A A; Potter, B
Abstract : A questionnaire was sent to 41 ethical committees in Scotland requesting information about their constitution and supervision of clinical research. Thirty-four (83%) replies were received. Committees varied in size from one to 73 members, most of whom were medical. Ten had no nurse members and only three had lay members without direct NHS connections. Sixteen saw their role as advisory rather than supervisory. Thirteen had not met in the past year whereas two had held 10 or more meetings. Limited use (12) was made of standard protocols, and only six had formal procedures for monitoring research in progress. Only seven of 370 proposals were rejected outright. Risk/benefit dilemmas and difficulties relating to informed consent were the commonest problems encountered. The committees provide only limited safeguards for patients and research workers, and more effective, standardised procedures are indicated.